Potential Biomass Evaluation on Forest Plant Stands In Aceh Province, Indonesia: A Case Study of Forest Product Utilization Permit for Cultivated Forest Area by PT. Acehnusa Indrapuri - Hairul Basri; Dahlan D; Deden Nurochman (Graduate Program of Syiah Kuala University, 2012)
Abstract – Development of industrial forest plantation currently has a primary function to produce timber for the fulfillment of the pulp and paper industry raw matter. In times of growing trees plantations have the ability to absorb carbon dioxide gases (CO2) in the atmosphere throught the process of photosynthesis which builds biomass stands and produce oxygen gases (O2). The potency of forest stands biomass and build a model standing stock biomass using the Normalized Difference Vegetation Index (NDVI) value from Satellite Imagery was investigated. Types of crops grown in Forest Product Utilization Permit for Cultivated Forest Area in PT.Acehnusa Indrapuri are A.mangium and E.urophylla plantations with area approximately 15,500.59 ha. The results showed the biomass content at the lowest value 16.81 tons per hectare with the NDVI Value of 0.342 whereas the highest content of biomass amounted to 145.750 tons per hectare in NDVI value 0.813. The content of plant biomass of forest stands can be expected by NDVI values using the model equation Y = 250.32 X 2 -15.221X- 3.3623 with R2 of 97.27%